2005
DOI: 10.1007/s00284-005-7529-3
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Two Novel Genes, cry24B and s1orf2, from a Mosquitocidal Strain of Bacillus thuringiensis serovar sotto

Abstract: Two new crystal protein genes, cry24B and s1orf2, were cloned from a mosquitocidal Bacillus thuringiensis serovar sotto strain. The cry24B and s1orf2 genes encoded a 76-kDa and 62-kDa protein, respectively. The Cry24B protein retained five conserved regions commonly found in the existing Cry proteins. The amino acid sequence of the S1ORF2 had a high homology to that of the ORF2 protein of B. thuringiensis serovar jegathesan. Southern hybridization experiments with a cry24B gene-specific probe revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…According to the pBtoxis plasmid sequence, these sequences exist, but lack their N-terminal half. Several reports support this observation as well as natural disconnections of the N-terminal half from its C-terminal half (Ito et al 2002;Ohgushi et al 2005;Hernández-Soto et al 2009;Noguera and Ibarra 2010;Barboza-Corona et al 2012;Sun et al 2013). In any case, this validation indicated that the developed HMM profile was able to detect any C-terminal sequence of a Cry protein, independently of the presence of its N-terminal half.…”
Section: Discussionsupporting
confidence: 55%
“…According to the pBtoxis plasmid sequence, these sequences exist, but lack their N-terminal half. Several reports support this observation as well as natural disconnections of the N-terminal half from its C-terminal half (Ito et al 2002;Ohgushi et al 2005;Hernández-Soto et al 2009;Noguera and Ibarra 2010;Barboza-Corona et al 2012;Sun et al 2013). In any case, this validation indicated that the developed HMM profile was able to detect any C-terminal sequence of a Cry protein, independently of the presence of its N-terminal half.…”
Section: Discussionsupporting
confidence: 55%
“…Figure 1 shows the configuration of various mosquitocidal Bt toxin genes including cry10A [16], cry19A [17,18], cry24B [19], cry30C [20], cry39A [21], cry40A (GenBank accession No. AB074414), cry44A [22], and cry59A [23].…”
Section: Separate Crystallization Domain Orfmentioning
confidence: 99%
“…In vivo recombination, therefore, appears to be a promising approach to the creation of new B. sphaericus strains for vector control [86]. The results suggested that the Cry27A protein is responsible for the Anopheles-preferential toxicity of the B. thuringiensis serovar high strain [87]. These inclusions exhibited no larvicidal activities against three mosquito species: Aedes aegypti, Anopheles stephensi and Culex pipiens molestus.…”
Section: Transgenic Mosquitoesmentioning
confidence: 99%